2022
DOI: 10.1007/s12072-021-10293-5
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Drum Tower Severity Scoring (DTSS) system for pyrrolizidine alkaloid-induced hepatic sinusoidal obstruction syndrome

Abstract: Background and aims There has been no reliable severity system based on the prognosis to guide therapeutic strategies for patients with pyrrolizidine alkaloid (PA)-induced hepatic sinusoidal obstruction syndrome (HSOS). We aimed to create a novel Drum Tower Severity Scoring (DTSS) system for these patients to guide therapy. Methods 172 Patients with PA-HSOS who received supportive care and anticoagulation therapy in Nanjing Drum Tower Hospital from January… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Furthermore, patients were all Chinese and received standard care in China, our findings require validation before generalizing to other populations with different settings. At last, we did not use DTSS grading system which was dedicated to PA-HSOS [19] due to lack of important data, such as peak portal vein velocity. Despite the limitations, the current study advances our knowledge on how to select patients for early intervention and provides preliminary results to support anticoagulant therapy for this special population.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, patients were all Chinese and received standard care in China, our findings require validation before generalizing to other populations with different settings. At last, we did not use DTSS grading system which was dedicated to PA-HSOS [19] due to lack of important data, such as peak portal vein velocity. Despite the limitations, the current study advances our knowledge on how to select patients for early intervention and provides preliminary results to support anticoagulant therapy for this special population.…”
Section: Discussionmentioning
confidence: 99%
“…Anticoagulation-TIPS step therapy is the most common treatment modality for acute or subacute PA-HSOS [ 8 , 17 , 18 , 19 ]. In addition, previous studies have shown that TIPS reverses progression in patients who have failed anticoagulation for PA-HSOS, with significant reductions in PP after TIPS treatment and survival rates of 80–90% [ 17 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…We also used the Drum Tower Severity Scoring (DTSS) to evaluate the severity of the PA-HSOS patients and the DTSS included fibrinogen, total bilirubin, portal vein velocity, and AST as parameters. Patients with a score of 4 to 6 were defined as mild, with a score of 7 to 10 were moderate, and with a score of 11 to 16 were severe [15]. The inclusion criteria were as follows: (1) age between 18 and 80 years old, (2) clear diagnosis of PA-HSOS (according to the 'Nanjing criteria'), and (3) unresponsive to initial short-term anticoagulation therapy.…”
Section: Introductionmentioning
confidence: 99%